(Substituted Ylidene)Amino‐2‐Oxo‐Indolylidene Thioureas and Bis(2‐Oxo‐Indolylidene)Urea from (Ylidene)Thiocarbonohydrazides and Isatylidene Malononitrile. (6th May 2016) - Hassan, Alaa A.; Mohamed, Shaaban K.; Abdel‐Latif, Fathy F.; Mostafa, Sara M.; Abdel‐Aziz, Mohamed; Mague, Joel T.; Akkurt, Mehmet; Bräse, Stefan; Nieger, Martin
Abstract : A simple and efficient synthesis of (substituted ylidene)(2‐oxoindolylidene)thiocarbohydrazones and bis(2‐oxoindolylidene)urea was achieved by the reaction of (substituted ylidene)thiocarbonohydrazides with isatylidene malononitrile. Rational for this conversation involving thenucleophilic additions on the dicyanomethylene carbon atom is presented. The structures of the products have been confirmed by using spectral and single‐crystal X‐ray analyses. Abstract :